ANALISIS SISTEM ANTRIAN PADA LOKET PELAYANAN UNTUK OPTIMALISASI PELAYANAN DI KPP PRATAMA SUKOHARJO - Aris Tri Wahyono; Erni Widajanti; Sunarso Sunarso (Universitas Slamet Riyadi, 2020)
The purpose of this study was to analyze service optimization, optimization of service time, and average customer waiting time at KPP Pratama Sukoharjo. This type of research is a case study at KPP Pratama Sukoharjo. The type of data uses qualitative and quantitative data. Data sources use primary and secondary data sources. The data analysis technique used in this study is a multiple queue model (M/M/S) where two or more individuals can be served at the same time by service facilities. Determination of the number of samples in this study using non-probability sampling technique with a sample size of 100 customers. The results showed that the average time spent serving a customer at KPP Pratama Sukoharjo at counter A is 7.1466 minutes, counter B is 4.116 minutes, counter C is 9,636 minutes and counter D is 5.5248 minutes. The average waiting time spent by customers to wait in the queue at KPP Pratama Sukoharjo at counter A is 0.001656 minutes, counter B is 0.0009852 minutes, counter C is 0.005373 minutes, and counter D is 0.0005316 minutes. The hypothesis in this study is that the average service time and average waiting time spent by customers to wait in queues at the service counters at KPP Pratama Sukoharjo are optimal with service time and average waiting time customers spend waiting in the queue ≤ 10 minutes. The set time standard reaches the level of optimization. This is indicated by the results of calculations that have been done with the method (M/M/S), the value is